ANALISIS PENERAPAN AKUNTANSI KEUANGAN DESA PADA PEMERINTAHAN DESA TEKULAI HULU KECAMATAN TANAH MERAH - HAPSAH ABBAS; NOVRIANI SUSANTI; RIA FEBRINA; BADEWIN BADEWIN (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This research was conducted at the Tekulai Hulu Village Office with the aim of analyzing and evaluating the level of conformity of the implementation of village financial accounting with Generally Accepted Accounting Principles (GAAP) and applicable government accounting provisions. Primary data were obtained through interviews with village officials, while secondary data were sourced from official documents such as the General Cash Book, Village Bank Book, APBDes reports, inventory lists, and other supporting documents. Data collection techniques were carried out through interviews and documentation. Data processing used a descriptive approach by grouping and presenting data based on relevant accounting theory. The research findings indicate that accounting practices in Tekulai Hulu Village do not fully comply with GAAP. Problems found include the implementation of a single-entry recording system, the use of a pure cash basis, incomplete preparation of general ledgers and trial balances, and the presentation of village wealth reports that do not comply with regulations. The use of Siskeudes in village financial management also does not reflect the comprehensive application of public sector accounting standards